Development of Thiazolidinone-Based Pyrazine Derivatives: Synthesis, Molecular Docking Simulation, and Bioevaluation for Anti-Alzheimer and Antibacterial Activities - Uzma Jehangir; Shoaib Khan; Rafaqat Hussain; Yousaf Khan; Farhan Ali; Asma Sardar; Samina Aslam; Mozhgan Afshari (Journal of Chemistry)
It is well recognized that heterocyclic compounds have exceptional biomedical applications, which has led scientists to become increasingly interested in their use in this field in the recent past. It is the aim of this study, using a multistep method based on thiazolidinone derivative synthesis, to synthesize thiazolidinone derivatives derived from pyrazine molecules (1–12). As a result of analyzing 1H-NMR, 13C-NMR, and HREI-MS data, the structures of these derivatives were determined. The minimum inhibitory concentration (MIC) of these drugs was also determined alongside the donepezil (IC50 = 10.10 ± 0.10 µM) to determine their potential as anti-Alzheimer agents. Among the screened derivatives, 1 (IC50 = 4.10 ± 0.20 µM), 2 (IC50 = 2.20 ± 0.20 µM), 4 (IC50 = 2.30 ± 0.20 µM), 5 (IC50 = 5.80 ± 0.30 µM), 6 (IC50 = 6.30 ± 0.20 µM), 8 (IC50 = 5.20 ± 0.10 µM), 9 (IC50 = 5.20 ± 0.40 µM), 10 (IC50 = 8.30 ± 0.40 µM), and 11 (IC50 = 8.10 ± 0.70 µM) showed potent activity. In addition, the synthesized moieties were screened against E. coli to determine whether there were any antimicrobial properties. It was found that most of the compounds were more potent inhibitors of bacterial growth in comparison to streptomycin, the reference drug. There have been several molecular docking experiments conducted to gain a deeper understanding of how these compounds interact with the active sites of enzymes to gain a greater understanding of their functional mechanisms.